Conductas sexuales de riesgo para la infección por el VIH/SIDA del personal del Fuerte Militar Héroes de Chacras durante el mes de octubre del 2008 - Gaona Moreno, Verónica M. (2010)
The present investigation was beginning the month on October 2008, in the force military Héroes de Chacras, in Machala city, I had a begging group very different of military people the Brigada of Infantería N°1 El Oro. They were survey 200 persons according them knowledge, attitude and sexual practice by rish for infection with the VIH-SIDA.